Bioinspired Hierarchical Structures for Contact‐Sensible Adhesives. (5th November 2021) - Hu, Hong; Wang, Duorui; Tian, Hongmiao; Huang, Qiyao; Wang, Chunhui; Chen, Xiaoliang; Gao, Yuan; Li, Xiangming; Chen, Xiaoming; Zheng, Zijian; Shao, Jinyou
Abstract: Bioinspired structural adhesives that are capable of bonding two objects together have recently found widespread applications in industrial fields, because of their promising reusability and environmental friendliness. However, such adhesives are usually monofunctional and cannot yield real‐time detection on the adhesion status, which is important for both biological systems (e.g., Gecko) and engineered mimics. This study reports a new hierarchical structure with the monolithic integration of adhesion and sensing functions, namely, contact‐sensible adhesive (CSA). The proposed CSA is composed of mushroom‐shaped microstructures on the top layer for providing strong adhesion, and a pillar array sandwiched by a pair of foil electrodes on the bottom layer as a compliant backing and a capacitive sensor. The CSA is not only sensitive to the external pressure, tension, and shear loads, but also shows enhanced adhesion on uneven surfaces, due to the high compliance of the hierarchical system. As a proof of concept, the as‐prepared CSA is applied as a contact interface in a gripper to complete the grasping task. Abstract : Bioinspired contact‐sensible adhesive (CSA) is achieved by a hierarchical architecture with mushroom‐shaped structures on the top layer and a capacitive force sensor on the bottom as a compliant backing. The CSA not only is sensitive to different types of external loads in normal and lateral directions, but also maintains a strong adhesion on the uneven surface.